Is tooth conservation possible in odontogenic sinusitis? Prospective evaluation of affected teeth condition-based protocol. (3rd January 2023) - Ito, Akiko; Nakaya, Muneo; Tada, Kazuhiro; Kumada, Junko; Kida, Wataru; Inayoshi, Yasuhiro
Abstract: Background: Affected tooth conservation is an often-overlooked problem in odontogenic sinusitis (ODS) treatment. Treatable dental conditions are improperly managed with extractions imposing an unnecessary health burden on patients. Furthermore, no down-to-earth protocols have been proposed for the clinical management of these patients. Aim: This study aims to prospectively validate a treatment protocol for ODS based on dental mobility, an indirect sign of poor long-term tooth survival. The protocol suggests endoscopic sinus surgery (ESS) alone followed by dental treatment for immobile affected teeth, and concomitant ESS and extraction for mobile teeth. Extraction of immobile teeth is considered if inflammation persists after the treatment. Material and methods: Forty cases treated with our protocol were prospectively examined about ODS cure and preservation of affected teeth. Results: Among the 35 patients with immobile affected teeth, only one required extraction for complete ODS cure after ESS. All five cases with mobile teeth and one with postoperative extraction had marginal periodontitis. Conclusion and significance: Ninety-seven percent of immobile affected teeth were preserved with complete ODS cure in this study. In case marginal periodontitis is present, extraction is likely to be necessary, although ESS should be prioritized over blanket extractions to preserve the teeth for patients' quality life.